DOMESTICATION OF SOME MEDICINAL TREES IN UGANDA - Stangeland, T. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Most rural communities in developing countries rely on medicinal plants for their health care. Unfortunately, important medicinal trees are threatened by overexploitation and landuse changes. Important trees need to be conserved. This requires a good understanding of their seed and germination ecology. In this study we investigated the influence of temperature and light on germination and seedling growth of two locally threatened medicinal trees, Hallea rubrostipulata and Sarcocephalus latifolius, in order to facilitate their establishment. Both species needed light to germinate. H. rubrostipulata had a temperature optimum of 25oC with 79 % germination, while for S. latifolius the total germination after 28 days was close to 60 % at temperatures from 20 to 35oC. Seedlings of S. latifolius survived well at 35oC, while those of H. rubrostipulata died at this high temperature. Conversely seedling of S. latifolius died at the low temperature of 15oC. We have chosen the Framework species method for reforestation. We raised seedlings of 38 different, mostly indigenous, trees in nursery for 6 to 12 months. The trees are a mixture of medicinal, firewood, fruit trees and trees useful for soil conservation. In the early rainy season in April 2008 we planted the same mixture of trees in three plots, each 40 x 40 m big. The trees were monitored two weeks after planting for height, crown width, root collar diameter and health. The plots are weeded three times during the rainy season, and growth is monitored once a month for one year.